2021
DOI: 10.1038/s41598-021-97909-w
|View full text |Cite
|
Sign up to set email alerts
|

Joint changes in RNA, RNA polymerase II, and promoter activity through the cell cycle identify non-coding RNAs involved in proliferation

Abstract: Proper regulation of the cell cycle is necessary for normal growth and development of all organisms. Conversely, altered cell cycle regulation often underlies proliferative diseases such as cancer. Long non-coding RNAs (lncRNAs) are recognized as important regulators of gene expression and are often found dysregulated in diseases, including cancers. However, identifying lncRNAs with cell cycle functions is challenging due to their often low and cell-type specific expression. We present a highly effective metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…With reference to EMSLR, it was proved to be essential for tumor-related phenotype. Cell-cycle phase distribution and proliferation reduction can be observed in lung cancer and colon cancer when depleting it (Hegre et al, 2021;Priyanka et al, 2022). Additionally, we estimated the expression of these several prognostic NLRs and found that it was basically consistent with the former bioinformatic analysis.…”
Section: Figuresupporting
confidence: 73%
“…With reference to EMSLR, it was proved to be essential for tumor-related phenotype. Cell-cycle phase distribution and proliferation reduction can be observed in lung cancer and colon cancer when depleting it (Hegre et al, 2021;Priyanka et al, 2022). Additionally, we estimated the expression of these several prognostic NLRs and found that it was basically consistent with the former bioinformatic analysis.…”
Section: Figuresupporting
confidence: 73%
“…Liao et al, reported that lncRNA FRGCA was highly expressed in colon adenocarcinoma and correlated with poor prognosis [ 56 ]. Hegre, S et al, reported that an oncogenic role of EMSLR, possibly by interfering with the progression from G1 to the S phase of the cell cycle [ 57 ]. Zhou et al, reported that MIR193BHG was one of the six pyroptosis-related lncRNAs prognostic signature for renal clear cell cancer prognosis prediction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Jiang et al revealed that SNHG26 stimulated PGK1/AKT/mTOR signaling pathway to promote tumor growth, metastasis, and chemotherapy resistance 41 . Hegre et al illuminated that knockdown of SNHG26 could interfere with the phase distributions of the cell cycle and reduce cell proliferation 42 . It is worth noting that a recent study analogously used SNHG26 to establish a prognostic signature of tumor immune infiltration-related lncRNAs in colon cancer, which confirmed the indispensable role of SNHG26 in the prognosis 43 .…”
Section: Discussionmentioning
confidence: 99%